Dampak Penghargaan dan Pengakuan terhadap Motivasi Berprestasi dan Profesionalisme Guru Bahasa Indonesia (Jurnal Motivasi Pendidikan dan Bahasa, 2024)
Education plays a crucial role in the development and survival of a nation. Teachers as the main actors in the educational process have a big responsibility in achieving successful quality education. This research aims to examine the impact of awards and recognition on the achievement motivation and professionalism of Indonesian language teachers. The research method is a qualitative approach with in-depth interview techniques, a hypothetical case study conducted on five Indonesian language teachers from two different schools. The research results reveal that awards increase work morale, encouragement to innovate, and teachers' intrinsic motivation. Recognition also has a significant impact on professionalism by increasing commitment, performance standards, and collaboration between teachers. Effective forms of reward include financial rewards, public recognition, and personal development opportunities. However, challenges such as consistency, fairness and sustainability in reward systems still need to be addressed. This research confirms the importance of rewards and recognition in increasing teacher motivation and professionalism, as well as contributing to improving the overall quality of education.